Gender audit committee and audit delay - Maria M Ratna Sari (The Indonesian Accounting Review, 2014)
The longer the time of audit delay, the more it shows the existence of problem in preparing financial statements by management. Besides that, it also indicates a lack of transparency and poor corporate management environment. Gender is one of the individual factors that influence work attitude. Physical specialization of the gender (male and female) illustrates the differences in implementing social activities. This study examined the effect of gender audit committee on audit delay by using regression analysis. It uses public companies listed in the Indonesia Stock Exchange which are determined based on judgment sampling. The results provide empirical study that gender audit committee affects audit delay with a significance level of 0.042 and give support to the gender roles theory that women perform the task better than men, so that the greater the number of women in the audit committee composition , the less the audit delay.